Optimization of Fortune Cooking Oil Distribution Routes Using Ant Colony Optimization Method - Yuniar Nur Latifah; Donoriyanto, Dwi Sukma; Nur Rahmawati (AI Society & STMIK Indonesia, 2024)
In Indonesia, cooking oil is very important as a food ingredient. Where the production volume of a product can affect distribution system decisions. An efficient distribution process can provide a competitive advantage in terms of cost and service. Distribution at PT ABC is currently still done manually, besides that the company has not optimized the transport capacity of vehicles so that it results in swelling distribution costs, as well as distribution bridges. This research is aimed at finding the most optimal distribution route for cooking oil products at PT A using the Ant Colony Optimization method. After processing the data using the Ant Colony Optimization method, the optimal fortune cooking oil distribution route was obtained by dividing it into 4 subroutes with a total mileage of 2371 KM with a total distribution cost of Rp. 1,612,960. and the total mileage of the initial route was 2693 KM with a total distribution cost of Rp. 1,831,240. So we get a total savings in mileage of 322 KM and savings in total distribution costs of Rp. 218,960. Therefore, the results obtained using the Ant Colony Optimization method will be selected as the proposed method.